2021
DOI: 10.1038/s41598-021-81877-2
|View full text |Cite
|
Sign up to set email alerts
|

Time trends of colorectal cancer incidence and associated lifestyle factors in South Korea

Abstract: Worldwide, South Korea had the second highest incidence rates of colorectal cancer (CRC) in 2018. To inform public health policy to prevent CRC, we aimed to identify major modifiable lifestyle factors underlying the alarming increase in CRC incidence. We obtained information on CRC statistics from the Korea National Cancer Incidence Database and on the distribution of dietary and lifestyle factors known to modify CRC risk from the Korea National Health and Nutrition Examination Survey. To examine time trends b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 39 publications
(64 reference statements)
1
30
0
Order By: Relevance
“…The same gender difference was seen in previous study in China, 16 Canada 17 and South Korea. 18 Smoking, obesity, alcohol drinking and physical inactivity appeared to be more relevant CRC contributor to men. 15 , 18 , 19 Commonly, Chinese men smoke more frequently than women.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The same gender difference was seen in previous study in China, 16 Canada 17 and South Korea. 18 Smoking, obesity, alcohol drinking and physical inactivity appeared to be more relevant CRC contributor to men. 15 , 18 , 19 Commonly, Chinese men smoke more frequently than women.…”
Section: Discussionmentioning
confidence: 95%
“… 18 Smoking, obesity, alcohol drinking and physical inactivity appeared to be more relevant CRC contributor to men. 15 , 18 , 19 Commonly, Chinese men smoke more frequently than women. 20 , 21 Furthermore, research results 19 showed that the transverse colon length of women was longer than that of men in colonoscopy, leading to a lower sensitivity to colorectal cancer screening in women.…”
Section: Discussionmentioning
confidence: 95%
“…Colorectal cancer (CRC) is a common and life-threatening disease worldwide [ 1 ], with Asia contributing the highest, 1, 009,400 (52.3%) of incident cases and 506, 499 (54.2%) of deaths in 2020 [ 2 ]. South Korea in 2018 had the second highest incidence rate of CRC in Asia, with currently positioning it at the fourth most common cause of cancer death [ 3 , 4 ]. Many population data reported that approximately 30–40% of CRC cases occur in patients aged above 75 years [ 1 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, 1.9 million cases of CRC were estimated worldwide [1]. In particular, South Korea had the second highest incidence rate of CRC in the world, as of 2018 [2]. Considering this increasing prevalence, accurate prediction of prognosis in patients with CRC after treatment is now essential.…”
Section: Introductionmentioning
confidence: 99%